Anaesthesia-Specifi c Oxygen Transport Assessment in Robot-Assisted Pelvic Surgery: a Clinical Trial - I. I. Lutfarakhmanov; S. T. Lazarev; N. A. Zdorik; A. D. Lifanova; A. A. Grazhdankin; I. R. Galeev; I. I. Musin; P. I. Mironov; V. N. Pavlov (Креативная хирургия и онкология, 2021)
Background. Robot-assisted pelvic surgery rapidly becomes a choice in surgeries for gynaecological oncology and urology. These interventions require special settings (pneumoperitonaeum and Trendelenburg position), which inevitably and systemically impact oxygen transport. Low oxygen delivery during surgery associates with manifold adverse outcomes. A single universal oxygen delivery threshold is impractical, as oxygen consumption must be taken into account. This study examines the effects of pneumoperitonaeum and Trendelenburg position on oxygen transport in patients of ASA functional class I–III (as per American Society of Anaesthesiologists).Materials and methods. Delivery, consumption, oxygen extraction, perioperative adverse events and type of general anaesthesia were prospectively studied in 126 adult patients.Results and discussion. Mean oxygen consumption was 242 mL/min/m2 , mean oxygen delivery — 612 mL/min/m2 . Oxygen delivery was below median 529 mL/min/m2 in 54 (43  %) patients. Perioperative adverse events developed in 36 (29 %) patients. A strong correlation (r > 0.500; p<0.001) between oxygen delivery and consumption was observed in 54 patients. Blood lactate level of 2.7 mmol/L at surgery end was indicative of inadequate oxygen delivery.Conclusion. No relationship was revealed between oxygen delivery and adverse perioperative events, and neither — between oxygen delivery and consumption relative to a particular anaesthetic.